Redistribution and Education Subsidies are Siamese Twins - A. Lans Bovenberg; Bas Jacobs (Tinbergen Institute, 2005)
We develop models of optimal linear and non-linear income taxation with endogenous human capital formation to explore optimal education subsidies. Optimal subsidies on education ensure efficiency in human capital accumulation and thus play an important role in alleviating the tax distortions on learning induced by redistributive policies. If the government cannot verify all investments in human capital, education policy offsets some but not all tax-induced distortions on learning. Non-pecuniary educational costs (benefits) may increase (decrease) subsidies on education, especially if they are complementary to work effort.
Keywords: H2; H5; J2; 330; human capital; education subsidies; progressive taxation; redistribution; Bildungsfinanzierung; Bildungsertrag; Einkommensteuer; Optimale Besteuerung; Kapitalertragsteuer; Theorie